Characteristics of interspecific hybridization and inbred progeny of pumpkin (Cucurbita moschata Duch.) and winter squash (Cucurbita maxima Duch.) - Liu, Zefa; Jiang, Yanfang; Yang, Xipeng; Deng, Xin; Dang, Jiancheng; Wang, Zhijun; Yusop, Mohd Rafii; Abdullah, Shamsiah (MDPI, 2022)
Hybrid incompatibility and F1 hybrid dysgenesis in the interspecific hybridization between pumpkin (Cucurbita moschata Duch.) and winter squash (Cucurbita maxima Duch.) have been previously noted. For this reason, it is difficult to obtain F2 generations due to F1 sterility. However, back-crossing and add-crossing can be utilized to overcome these incompatibility barriers in interspecific hybridization. To date, few studies have focused on parental selection, the back-crossing process, and offspring characteristics related to interspecific hybridization. Hence, we explored the F1 seed acquisition rate, plant characteristics, and F2 generation fertility after interspecific back-crossing and add-crossing hybridization of C. moschata and C. maxima. Moreover, as a female parent, X-1 (C. moschata) yielded F1 seeds when crossed with winter squash (C. maxima) 10-04-3, 10-37, or 10-05-2. BC1F1 seeds and plants could be obtained with winter squash (C. maxima) as the recurrent parent. Some healthy F2 seeds and plants were obtained from the interspecific hybrids, including ZJ-13, ZJ-8, and ZJ-11. Further fruit nutrition quality analysis showed that the starch, polysaccharide, cellulose, and dry material contents of ZJ-7 and ZJ-8 were significantly higher than those of the parent pumpkin and winter squash lines. The bioflavonoid content of ZJ-8 was lower than that of its parents, and its soluble protein was at the median value. Meanwhile, the bioflavonoid content of ZJ-1 was lower than that of its parents, but its soluble protein was significantly higher. These results suggest that back-crossing and multi-crossing can overcome the barriers to interspecific crossing of C. moschata × C. maxima. Some interspecific hybrid fruits had nutritional contents much higher than those of their parent lines. Additionally, X-1 (C. maxima) was found to act as a bridge species in interspecific hybridization. Collectively, in this study, the barriers to interspecific hybridization of C. moschata × C. maxima were addressed through crossing methods and choice of parents, and the obtained results are expected to provide novel support for interspecific hybrid breeding between C. moschata and C. maxima.